Correction to: Time Trends in Adolescent School Absences and Associated Bullying Involvement Between 2000 and 2019: A Nationwide Study. - Alanko, K.; Melander, K.; Ranta, K.; Engblom, J.; Kosola, S. (Child Psychiatry & Human Development, 2025)
The main focus of the article is a correction regarding the misrepresentation of Dr. Katarina Alanko's name in a previously published article. The correction clarifies that her name was incorrectly displayed as E. G. Katarina Alanko instead of the accurate K. Alanko. This correction has been officially published to rectify the error in the original article. The publisher, Springer Nature, maintains a neutral stance on jurisdictional claims related to published maps and institutional affiliations.